Representation of Madura Cultural Tourism in Indonesian Poetry Discourse (Tourism Literature Study) - Syaiful Rahman; Djoko Saryono; Karkono Karkono (RIRAI Publisher, 2022)
The purpose of this study was to describe Madura tourism contained in a collection of Indonesian poetry books. The method used in this study was descriptive qualitative with a tourism theory approach. Data was the form of words and sentences that represent Madura cultural tourism, while the data source in this study came from a collection of Indonesian poetry with the theme of tourism. The instrument used for data collection in this study was the researcher himself. The data collection technique in this study was carried out with the note-taking method, with the work steps of reading repeatedly the collection of Indonesian poetry books, outlining the selected data, and recording data. To analyze the data in this study, researchers used the Milles & Huberman model by adjusting the needs. The results showed that there were 14 collections of Indonesian poetry books with the theme of Madura cultural tourism, consisting of 69 poetry titles, 121 data were found, with details of 105 data representing Madura traditional tourism and 16 data representing Madura art tourism. The representation of tourism in Indonesian poetry would ultimately have an impact on the introduction, preservation, and development of Madurese culture as a tourism object.